Antibacterial activity of SPIONs versus ferrous and ferric ions under aerobic and anaerobic conditions: a preliminary mechanism study. Issue 2 (8th January 2020) - Gholami, Ahmad; Mohammadi, Fatemeh; Ghasemi, Younes; Omidifar, Navid; Ebrahiminezhad, Alireza
Abstract : In modern medicine, major attention has been paid to superparamagnetic iron oxide nanoparticles (SPIONs). Recent studies have shown the antibacterial properties of SPIONs against some Gram‐positive and Gram‐negative bacterial strains. These nanoparticles (NPs) can bind to bacterial membranes via hydrophobic or electrostatic interactions and pass through cell barriers. In this study, the authors evaluated the antibacterial activity of magnetic NPs in comparison with ferrous and ferric ions. The level of reactive oxygen species (ROS) in the treated Staphylococcus aureus and Escherichia coli bacteria were directly measured by fluorometric detection. The results showed that iron ions and SPIONs had significant dependent antimicrobial activities. SPIONs showed greater inhibitory effects than ferrous and ferric ions against the growth of treated bacterial strains under anaerobic conditions, while in aerobic conditions, ferrous showed the strongest antibacterial activity. In anaerobic conditions, they observed the greatest ROS formation and lowest minimum inhibitory concentration in the SPION‐treated group in comparison with the other groups. It seems that the release of iron ions from SPIONs and subsequent activation of ROS pathway are the main antibacterial mechanisms of action. Nevertheless, the greater antibacterial effect of SPIONs in anaerobic conditions represents other mechanisms involved in the antibacterial activity of these NPs